Comparison of outdoor play spaces in low versus high socioeconomic early childhood development centres in Johannesburg - Clarkson, Lara Ferna (University of the Witwatersrand, Johannesburg, 2024)
Introduction: Play spaces facilitate play as a child’s primary occupation which is essential for learning and early child development. In South African early childhood development centres, almost 11% do not have access to outdoor play areas, 20% have no outdoor play equipment, and 50% have no access to educational toys (Statistics South Africa, 2016). Objectives: This research aimed to determine the physical design and availability of outdoor play spaces in low socioeconomic and high socioeconomic early childhood development centres in Johannesburg and make comparisons between the outdoor play space physical design and availability of these two control groups. Methods: A descriptive comparative research design was used, with a total population sampling method for the distribution of a self-developed research questionnaire adapted from play literature. Results were obtained from a total sample size of 82 early childhood development centres, 28 reported low socioeconomic and 54 reported high socioeconomic. Quantitative data was analysed using descriptive and inferential statistics. Qualitative data was analysed as a supplement using content analysis and photographic evidence. Results: Low socioeconomic early childhood development centres, 57% community- based sites, had significantly less funding frequency compared to high socioeconomic early childhood development centres, 83% independent / private schools, with 87% private funding at least annually for outdoor play space upkeep. Overall, low socioeconomic early childhood development centres had limited outdoor play space resource variety and quantity (7% had no outdoor play space, 43% had traditional playground designs, 14% had no fixed playground structures), compared to high socioeconomic early childhood development centres which had a wide variety and abundance of outdoor play space resources with 30% traditional and 33% creative playground designs. Chi-squared statistics revealed a significantly greater number of fixed manufactured equipment, loose manufactured materials, loose movement toys, fixed natural resources, loose natural resources, and multi-sensory exploration spaces in high socioeconomic early childhood development centres. Cramer’s V statistics revealed outdoor play space physical design and availability have a strong dependence on socioeconomic status.
A research report submitted in fulfillment of the requirements for the Master of Science in Occupational Therapy, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Outdoor play space; early childhood development; socioeconomic status; physical design; equipment; resource availability.; SDG-3: Good health and well-being